Late seed migration after prostate brachytherapy with Iod-125 permanent implants - Maletzki, Philipp (Prostate Int, 2018)
BACKGROUND: Seed migration is a common finding after low dose rate brachytherapy of the prostate. It has often been assessed soon after implantation, but little is known about late seed migration. We evaluated the incidence, site, symptoms, and therapeutic consequences of late seed migration more than 3 years postoperatively. MATERIALS AND METHODS: We retrospectively examined the data of 63 unselected patients with transrectal ultrasound-guided, transperineal low dose rate brachytherapy of the prostate with stranded seeds between 2001 and 2010. A pelvic X-ray was taken the day after implantation and after 6 weeks in combination with a pelvic computed tomography/magnetic resonance imaging scan (image fusion) for dosimetry. Late radiological follow-up with a further pelvic and chest X-ray was conducted 3 or more years postoperatively. We differed between seed loss without anatomical detection and seed migration into another anatomical region. RESULTS: We found seed loss up to 3 years and more after brachytherapy in 36 of 63 patients (57%). Between one and nine seeds had been lost. Late seed migration after 3 or more years occurred in two of 36 patients (6%), with pelvic migration of one seed and extrapelvic migration of one seed to the lung and two seeds to the liver, respectively. All late seed migrations were asymptomatic and had no therapeutic consequences. CONCLUSION: Beside a frequent number of seed losses, seed migration 3 or more years after implantation was as well a frequent finding but seems to be asymptomatic. Long-term follow-up with complementary radiological controls could be helpful in detecting any rare complications.